'Square Root' of the Maxwell Lagrangian versus confinement in general relativity - Mazharimousavi, S. Habib; Halilsoy, Mustafa (Physics Letters B, Elsevier, 2012)
We employ the 'square root' of the Maxwell Lagrangian (i.e. \surd(F_{{\mu}{\nu}}F^{{\mu}{\nu}})), coupled with gravity to search for the possible linear potentials which are believed to play role in confinement. It is found that in the presence of magnetic charge no confining potential exists in such a model. Confining field solutions are found for radial geodesics in pure electrically charged Nariai- Bertotti-Robinson (NBR)-type spacetime with constant scalar curvature. Recently, Guendelman, Kaganovich, Nissimov and Pacheva, [Phys.Lett.B704(2011)230] have shown that superposed square root with standard Maxwell Lagrangians yields confining potentials in spherically symmetric spacetimes with new generalized Reissner-Nordstr\"om-de Sitter / -anti-de Sitter black hole solutions. In NBR spacetimes we show that confining potentials exist even when the standard Maxwell Lagrangian is relaxed.
The file in this item is the publisher version (published version) of the article.
Keywords: general relativity; black holes